KONTEN SEKSUAL DALAM VIDEO KLIP DANGAP-DANGAP DEK ULIK DAN LOLAK - Ditha Sasmitha, Ni Wayan; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2018)
ABSTRACT Sexually charged information is broadcasting through various forms of communication media. This sexual content can be seen in a video clip that aired on television, CD albums and on social media Youtube. Dek Ulik and Lolak’s video entitled Dangap-Dangap has been watched until 900,000 times on Youtube. The purpose of this study was to find out the sexual content contained in the Dangap-Dangap video clip sung by Dek Ulik and Lolak. The type of research used is qualitative with constructivist pradigma. The primary data source in this study is the Dangap-Dangap video clip of Dek Ulik and Lolak uploaded on Youtube, as well as secondary data sources from literature relevant to research titles, such as books, journals, articles, online mass media, and papers. The research method used is Charles Sanders Peirce semiotic analysis method. The results of this study were the presence of mild and severe sexual behavior displayed in this Dangap-Dangap video clip. Mild sexual behavior is shown by the activities of fantasy, teasing, and hand movements represent the behavior of masturbation. Mild sexual behavior is shown by the activities of fantasy, teasing, and hand movements that refers to the behavior of masturbation and body movement that refers to sexual behavior as severe as mimic coitus. Keywords: Dangap-Dangap, Dek Ulik- Lolak’s Clip Video, Semiotics, Sexual Content.